Web-enabled data extraction system for cotton pests - SHARMA, RAKHEE; KUMAR, AMRENDER; TANWAR, R K; SINGH, NIRANJAN (The Indian Journal of Agricultural Sciences, 2018)
Under Online Pest Monitoring and Advisory Services (OPMAS) program, huge information/data on cotton pest along with weather were collected in three intensive cotton growing zones, viz. the North Zone (Punjab, Haryana and Rajasthan), the Central Zone (Maharashtra, Madhya Pradesh and Gujarat), and the Southern Zone (Andhra Pradesh, Telangana, Karnataka and Tamil Nadu), in India. Based on pest monitoring weekly advisory services were issued to extension agencies and farmers for control measures of pests in the cotton crop. Under the project extraction system was developed which was based on three tier architecture, i.e. presentation, application and data tier to reduce the effort for searching a huge set of data for desired information on real time points. In the system, the central value of pest (mean, maximum and minimum) and spread of the pest in terms of variance and standard deviation may be obtained. These results can provide the epidemic status of the pest based on the threshold values which can be utilized to issue advisories to farmers about the pest control. In future the data extracted from this system can be used for pattern development using pest population as a character under study and time variable as an independent/explanatory variable.